Tunable Terahertz Plasmonic Sensor Based on Graphene/Insulator Stacks - Yi Huang; Shuncong Zhong; Haizi Yao; Daxiang Cui (IEEE Photonics Journal, 2017)
We propose a layer-by-layer graphene/insulator stacks based terahertz plasmonic sensor of refractive index of testing samples using a prism-coupling attenuated total reflection configuration. An angular interrogation technique has been used to explore the performance of the sensor in terms of detecting accuracy, sensitivity, and figure of merit (FOM). From the analysis of theoretical resonance angle of the sensor and the finite element method (FEM) based simulation, we reveal that the number of graphene layer (N), the Fermi level energy $(E_{F})$ of graphene, and refractive index of testing samples have a great effect on these performance parameters. The simulated results show that more layers of graphene will result in higher detection accuracy but lower sensitivity and FOM. The effective detection accuracy can be improved through high doping levels or with multilayer graphene. The maximum detection accuracy is 7.14 degree–1 for $N\,= \,5$ at $E_{F}\,= \,{\rm{1.6\,eV}}$ . The maximum sensitivity is 51.0°/RIU, along with a FOM up to 12.75 RIU–1 for $N\,= \,1$ at $E_{F}\,= \,{\rm{1.0\,eV}}$ .